1996. Addressing Pulmonary Nocardiosis Risk in Immunocompromised Patients: Development and Validation of a Commercially Available PCR. (26th November 2018) - Smith, Emily; Bartlett, Katelyn; Grantham, James; Powell, Natalie; Altrich, Michelle; Kleiboeker, Steve; Wissel, Mark
Abstract: Background: Pulmonary nocardiosis is an infection targeting immunocompromised patients characterized by high mortality and requires nonfrontline antibiotics for treatment. Nocardiosis is currently confirmed or excluded by BAL fluid culture followed by further phenotypic identification steps. A culture-independent method with more timely results would accelerate the administration of appropriate treatment. A rapid Nocardia (NOC) PCR assay for BAL has neither been previously validated nor offered for clinical testing to our knowledge. Methods: Oligonucleotides for a rapid NOC PCR comprehensive of the causative agents of nocardiosis were aligned to the 16S regions of common NOC species and over 30 others. Specificity was verified against publically available bacterial 16S sequences. Rapid automated nucleic acid extraction (<1 hour for 24 samples) followed by fast PCR (<1 hour) was validated according to relevant compliance standards. Spiked/unspiked human BAL samples were used to assess analytical specificity, limit of detection (LOD), precision and accuracy using NOC and non-NOC strains. Results: The NOC PCR detected, among others, the most common NOC species ( N. cyriacigeorgica, N. nova, N. farcinica and N. brasiliensis ). We estimate more than 95% of causative agents of nocardiosis are detectable by the assay. No cross reactivity was detected from 30 non-NOC bacterial pathogens except for Rhodococcus and Crossiella spp. LOD in BAL fluid was determined to be 206, 41, and 26 copies/mL for N. cyriacigeorgica, N. nova, and N. transvalensis, respectively. Intra- and inter-assay precision studies revealed copies/mL %CV's of <10% and <8% at a high concentration and <21% and <26% at a low concentration, respectively. Accuracy studies yielded 100% concordance with 33 BAL positives and 20 BAL negatives. Conclusion: The specificity, inclusivity, sensitivity, precision and accuracy of a qualitative PCR have been deployed as an aid in the diagnosis of pulmonary nocardiosis. NOC PCR allows for a culture-independent method that can rapidly detect clinically relevant NOC species with an improved turnaround time, leading to prompt diagnosis and administration of appropriate treatment. Disclosures: E. Smith, Viracor Eurofins Clinical Diagnostics: Employee, Salary. K. Bartlett, Viracor Eurofins Clinical Diagnostics: Employee, Salary. J. Grantham, Viracor Eurofins Clinical Diagnostics: Employee, Salary. N. Powell, 1987: Employee, Salary. M. Altrich, Viracor Eurofins Clinical Diagnostics: Employee, Salary. S. Kleiboeker, Viracor Eurofins Clinical Diagnostics: Employee, Salary. M. Wissel, Viracor Eurofins Clinical Diagnostics: Employee, Salary.